2021
DOI: 10.4142/jvs.2021.22.e60
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic parameters and indices in 23 healthy Maltese dogs

Abstract: Background Echocardiography is a primary tool used by veterinarians to evaluate heart diseases. In recent years, various studies have targeted standard echocardiographic values for different breeds. Reference data are currently lacking in Maltese dogs and it is important to fill this gap as this breed is predisposed to myxomatous mitral valve disease, which is a volume overload disease. Objectives To establish the normal echocardiographic parameters for Maltese dogs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The results of this study and others showed no significant correlations between the functional parameters and age, which suggests that decreased FS is not a normal aging process [ 24 ]. LA/Ao is known to give a body-size-independent measurement of LA, and LA/Ao in this study was not influenced either by breed, age, or BW [ 21 , 22 , 23 , 26 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results of this study and others showed no significant correlations between the functional parameters and age, which suggests that decreased FS is not a normal aging process [ 24 ]. LA/Ao is known to give a body-size-independent measurement of LA, and LA/Ao in this study was not influenced either by breed, age, or BW [ 21 , 22 , 23 , 26 ].…”
Section: Discussionmentioning
confidence: 74%
“…In this study, functional parameters such as EF and FS did not show any significant association with breed, age, or BW. In the veterinary literature, there are mixed reports on the associations between BW and the functional parameters, where some reported the latter to be independent of BW [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while others revealed a negative correlation [ 4 , 19 , 22 , 23 , 24 , 25 ]. The results of this study and others showed no significant correlations between the functional parameters and age, which suggests that decreased FS is not a normal aging process [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure accurate interpretation of echocardiographic examinations in dogs, it is crucial to consider breed-specific reference values. Failing to do so can lead to misinterpretations, falsely indicating heart enlargement or altered activity when compared with general reference ranges, potentially resulting in misdiagnosis and inappropriate treatment [ 22 , 29 , 35 , 42 , 54 ]. The coefficients of variation for all echocardiographically measured parameters can range from 5.03% to 46.43%, with the majority falling below 20% [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Echocardiography was conducted using an ESAOTE MY LAB 40 eHD device with a 1.0-4.0 MHz phased array transducer. Breed-specific criteria were applied when appropriate [22,[38][39][40][41][42][43][44]. The examination followed existing guidelines and was performed on an echocardiographic table in right and left lateral recumbency.…”
Section: Animals and Group Assignmentmentioning
confidence: 99%
“…The echocardiographic assessment employed a conventional protocol encompassing 2-D, M-mode, spectral Doppler, and color Doppler techniques. This allowed for the classification and staging of dogs with dilated cardiomyopathy (DCM) according to established guidelines [22,[38][39][40][41][42][43][44][45]. The dogs exhibited echocardiographic changes indicative of systolic dysfunction, such as increased left ventricular (LV) end-systolic chamber diameter or end-systolic volume, reduced fractional shortening or ejection fraction, and increased E-point to septal separation.…”
Section: Animals and Group Assignmentmentioning
confidence: 99%